Measuring history : cases of state-level testing across the United States - Grant, S. G. (Research in curriculum and instruction., 2006)
Measuring History complements the cases presented in Wise Social Studies Practices (Yeager & Davis, 2005). Yeager and Davis highlight the rich and ambitious teaching that can occur in the broad context of state-level testing. In this book, the chapter authors and I bring the particular state history tests more to the fore and examine how teachers are responding to them. At the heart of Measuring History are cases of classroom teachers in seven states (Florida, Kentucky, Michigan, New York, Texas, Mississippi, and Virginia) where new social studies standards and new, and generally high-stakes, state-level history tests are prominent. In these chapters, the authors describe and analyze the state's testing efforts and how those efforts are being interpreted in the context of classroom practice. The results both support and challenge prevailing views on the efficacy of testing as a vehicle for educational reform. Catherine Horn (University of Houston) and I lay the groundwork for the case studies through a set of introductory chapters that examine the current environment, the research literature, and the technical qualities of history tests.